Investigation of graphene effect on the anti-corrosion behaviour of polyurethane coatings in sea-water. Issue 6 (20th August 2019) - Tan, Hai; Wang, Deguo; Guo, Yanbao
Abstract : Purpose: Abundant oil and gas reservoirs in the deep-water are the valuable non-renewable energy sources. However, sea-water could enhance the corrosion of marine equipment such as submarine pipe trees. Various coatings, for example, polyurethane (PU) coatings are sprayed on the steel surfaces to enhance the anti-corrosion performance. Thus, to improve the anti-corrosion behavior of PU coatings in sea-water is imperative. Design/methodology/approach: In this paper, the corrosion behaviors of 4130 carbon steel with and without PU coatings were discussed by electrochemical mean in sea-water. And the graphene additive in different concentrations (0.1, 0.3, 0.6 and 0.9 per cent) were also studied. A series of characterized methods were introduced to identify the anti-corrosion performances of 4130 carbon steel with and without coatings, respectively. Findings: The results showed that the anti-corrosion property of 4130 carbon steel can enhance obviously with the PU coatings. The graphene additive can further improve the anti-corrosion behaviour of PU coatings and in the concentration of 0.6 per cent the PU/graphene coatings worked best. Originality/value: This is beneficial for enhancing the service life of marine equipment in an eco-friendly method.